Exergy and Environmental Impact Assessment between Solar Powered Gas Turbine and Conventional Gas Turbine Power Plant - Ali Rajaei; Hasan Barzegar Avval; Elmira Eslami (International Journal of Chemical Engineering)
Recuperator is a heat exchanger that is used in gas turbine power plants to recover energy from outlet hot gases to heat up the air entering the combustion chamber. Similarly, the combustion chamber inlet air can be heated up to temperatures up to 1000 (°C) by solar power tower (SPT) as a renewable and environmentally benign energy source. In this study, comprehensive comparison between these two systems in terms of energy, exergy, and environmental impacts is carried out. Thermodynamic simulation of both cycles is conducted using a developed program in MATLAB environment. Exergetic performances of both cycles and their emissions are compared and parametric study is carried out. A new parameter (renewable factor) is proposed to evaluate resources quality and measure how green an exergy loss or destruction or a system as a whole is. Nonrenewable exergy destruction and loss are reduced compared to GT with recuperator cycle by 34.89% and 47.41%, respectively. Reductions in CO2, NOx, and CO compared to GT with recuperator cycle by 49.92%, 66.14%, and 39.77%, respectively, are in line with renewable factor value of around 55.7 which proves the ability of the proposed green measure to evaluate and compare the cycles performances.